2012
DOI: 10.1007/s11739-012-0837-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelets in NOX2 activation mediated by TNFα in heart failure

Abstract: Tumor necrosis factor (TNF) α may contribute to the deterioration of cardiovascular function in heart failure (HF) through various mechanisms, including the generation of reactive oxygen species (ROS). NADPH oxidase is the major source of ROS in the vascular system, but the interplay between TNFα and NADPH oxidase activation is elusive. As platelets possess NADPH oxidase enzyme, they represent an important tool to investigate the interplay between NADPH oxidase and TNFα in patients with HF. Serum gp91phox (NOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…There is evidence indicating that the expressions of NOX2 and NOX4 are markedly changed, accompanied by the activation of apoptosis [23]. Consistent with previous studies, here we found changed expressions of SOD and MDA in HF model, suggesting that induction of oxidative stress occurred during HF after MI [24]. Moreover, the two isoforms of NADPH oxidases were believed to cause apoptosis by inducing ROS [25].…”
Section: Discussionsupporting
confidence: 89%
“…There is evidence indicating that the expressions of NOX2 and NOX4 are markedly changed, accompanied by the activation of apoptosis [23]. Consistent with previous studies, here we found changed expressions of SOD and MDA in HF model, suggesting that induction of oxidative stress occurred during HF after MI [24]. Moreover, the two isoforms of NADPH oxidases were believed to cause apoptosis by inducing ROS [25].…”
Section: Discussionsupporting
confidence: 89%
“…17 It is important to note that TNF-α also acts as a potent inducer of ROS generation through impairment of mitochondrial biogenesis and activation of NADPH oxidase. 8,[18][19][20][21][22][23] Taken together, these data allow us to speculate that the immune system and the redox system might in some way interact synergistically, such that both mechanisms might be relevant in the pathogenesis of psoriasis.…”
Section: Introductionmentioning
confidence: 89%
“…TNF-α has been also shown to activate Nox1 NADPH oxidase in mouse fibroblasts when cells undergo necrosis. 22 Finally, an in vitro study carried out by Cangemi et al, 23 which was carried out in platelets from a subgroup of heart failure patients, showed that TNF-α (at concentrations commonly found in the peripheral circulation of heart failure patients) activates platelet NOX2. Thus, TNF-α increases ROS production and extracellular levels of NOX2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such interplay is useful to explain the tendency to venous and artery thrombosis in clinical settings, such as heart failure, cirrhosis, anoxia-reoxygenation, atrial fibrillation, and diabetes, all of which are characterized by the up-regulation of NOX2 and the over-expression of isoprostane (10,11,(20)(21)(22).…”
Section: Clinical Studiesmentioning
confidence: 99%